Demographic characteristics and consumer decision-making styles: Do they impact fashion product involvement? - Heba Abdel Wahab; Naglaa Mohamed Diaa; Sahar Ahmed Nagaty (Cogent Business & Management, 2023)
Consumer decision-making styles are considered as psychological and intellectual approaches that can influence the customer purchase decision and can help in explaining the behavior of customers toward fashion products. The purpose of this research is to analyze the impact of consumer decision-making styles on fashion product involvement, as well as the effect of demographic variables (age, gender, income, and education) on consumer decision-making styles and fashion product involvement. Data was gathered through an online questionnaire from a sample of 400 Egyptian customers of fashion products. Results revealed that consumer decision-making styles have a strong significant positive effect on fashion product involvement. The results also showed that all four demographic variables have a significant effect on fashion product involvement as well as on consumer decision-making styles. Research findings were discussed to reflect the researchers' interpretation and perception of the outcomes addressed.
Keywords: 650; consumer behavior; consumer decision-making styles; demographic variables; fashion industry; fashion product involvement